2022
DOI: 10.3390/cancers14030832
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Therapy for Oligoprogression in Patients with Metastatic NSCLC Harboring Activating EGFR Mutations

Abstract: After a variable period of activity of the epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) treatment, patients with advanced non-small cell lung cancer (NSCLC) harboring EGFR mutations develop resistance to these TKIs. In some cases, an oligoprogression is diagnosed, and its management is still controversial. The oligoprogression represents an intermediate stage of metastatic NSCLC between localized and widely disseminated disease, and is characterized by a limited number and/or sites of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Oligometastatic status was defined as a maximum of 5 metastases in 3 organs, but diffuse plasma membrane (meningeal, pleural, pericardial, and mesenteric) or bone marrow metastases were not included in this definition [18] . Oligoprogressive disease is a special condition, which is defined as disease progression at a limited number of anatomical sites (not more than 5 sites of progression and 2 organs), whereas there is continued response or stable disease at other sites, the biology of tumours is more inclined to be indolent [19] .…”
Section: Methodsmentioning
confidence: 99%
“…Oligometastatic status was defined as a maximum of 5 metastases in 3 organs, but diffuse plasma membrane (meningeal, pleural, pericardial, and mesenteric) or bone marrow metastases were not included in this definition [18] . Oligoprogressive disease is a special condition, which is defined as disease progression at a limited number of anatomical sites (not more than 5 sites of progression and 2 organs), whereas there is continued response or stable disease at other sites, the biology of tumours is more inclined to be indolent [19] .…”
Section: Methodsmentioning
confidence: 99%
“…Oligoprogression is a relatively new concept which has emerged as effective local therapies became available, referring to progressive lesions restricted in both number and involved sites, typically less than five. 63 , 64 …”
Section: Brain Progression On Osimertinib and What To Do?mentioning
confidence: 99%
“…Oligoprogression is a relatively new concept which has emerged as effective local therapies became available, referring to progressive lesions restricted in both number and involved sites, typically less than five. 63,64 Several real-world datasets have explored the patterns of disease progression after osimertinib. One report has suggested that EGFR T790Mpositive NSCLC patients treated with osimertinib are more likely to progress with oligoprogressive lesions (72%) than overt systemic progressive lesions (28%).…”
Section: Brain Progression On Osimertinib and What To Do?mentioning
confidence: 99%
“…Oligoprogressive lesions following SBRT for organ confined disease often first appear in the organ confined site before progressing to distant extra organ sites ( 17 ). In the situation of EGFR + NSCLC patients on tyrosine kinase inhibitor (TKI) therapy, most studies have indicated that the lung as the most common area of progression, with the CNS, and thoracic lymph nodes being the most common other site of progression ( 18 ). Other studies however have indicated the CNS as the most common site of oligoprogression for EGFR + NSCLC ( 19 ).…”
Section: Historical Perspectivementioning
confidence: 99%